Determinants of Individual Investor Behaviour in Stock Investment Decisions - Pahlevi, Reza Widhar; Oktaviani, Indri Irma (Postgraduate Program Merdeka University, 2018)
The quality of individual investor behavior in making stock investment decisions is very important to be understood as a reference of the movement of the capital market. This research using descriptive analysis technique, and inferential analysis, using Structural Equation Model (SEM), using the help of software PLS (Partial Least Square). The population used in this study are individual investors (student in Yogyakarta area) who actively transact on the Indonesia Stock Exchange. The sample used in this research is the investor who is still a member of the Capital Market Study Group (KSPM) at several universities in Yogyakarta. Based on the result of the research, It can be concluded that the attitude, subjective norm, perception of behavior control, subjective norm, overconfidence, excessive optimism, herd behavior have positive effect on investors' intention in investing, and there is no influence between psychology of risk to investor attitude in investing.The quality of individual investor behavior in making stock investment decisions is very important to be understood as a reference of the movement of the capital market. This research using descriptive analysis technique, and inferential analysis, using Structural Equation Model (SEM), using the help of software PLS (Partial Least Square). The population used in this study are individual investors (student in Yogyakarta area) who actively transact on the Indonesia Stock Exchange. The sample used in this research is the investor who is still a member of the Capital Market Study Group (KSPM) at several universities in Yogyakarta. Based on the result of the research, It can be concluded that the attitude, subjective norm, perception of behavior control, subjective norm, overconfidence, excessive optimism, herd behavior have positive effect on investors' intention in investing, and there is no influence between the psychology of risk to investor attitude in investing. Â DOI: https://doi.org/10.26905/afr.v1i2.2427